Intranasal Immunization with Inactivated Influenza Virus Enhances Immune Responses to Coadministered Simian-Human Immunodeficiency Virus-Like Particle Antigens - Kang, Sang-Moo (American Society for Microbiology, 2004)
Intranasal immunization with inactivated influenza virus vaccine can provide protective immunity, whereas many other antigens are less effective when used for mucosal immunization. To determine whether influenza virus could enhance immune responses to an antigen coadministered to a mucosal surface, we studied the intranasal immunization of mice with a mixture of simian-human immunodeficiency virus (SHIV) virus-like particles (VLPs) and inactivated influenza virus. Compared to mice immunized with SHIV VLPs alone, mice coimmunized with SHIV VLPs and inactivated influenza virus showed significant increases in serum immunoglobulin G (IgG) and mucosal IgA antibodies specific to the human immunodeficiency virus envelope protein, neutralizing activities, numbers of gamma interferon- and interleukin 4-secreting lymphocytes, and cytotoxic-T-lymphocyte activities. The levels of enhancement of immune response by coimmunization with inactivated influenza virus were equivalent to those induced by inclusion of immunostimulatory CpG oligodeoxynucleotides (CpG DNA). We also observed that SHIV VLPs bind to influenza virus virions, forming mixed aggregates. These results indicate that inactivated influenza virus can play a role as a mucosal adjuvant to coadministered antigens.